Effects of Embryonic Inflammation and Adolescent Psychosocial Environment on Cognition and Hippocampal Staufen in Middle-Aged Mice - Wu, Yong-Fang; Zhang, Yue-Ming; Ge, He-Hua; Ren, Chong-Yang; Zhang, Zhe-Zhe; Cao, Lei; Wang, Fang; Chen, Gui-Hai (Frontiers in Aging Neuroscience, 2020)
The Accumulating evidence has indicated both prenatal exposure to inflammation and youth psychosocial stress could accelerate the age-associated cognition impairments, which can be attributed to changes of synaptic plasticity-associated proteins, such as RNA-binding proteins (RBPs). Staufen is a double-stranded RBP that plays a critical role in the modulation of synaptic plasticity and memory. However, relatively few studies have investigated the effects of prenatal exposure to inflammation and youth psychosocial stress on the cognition and neurobiology of middle-aged people. Consequently, the aim of this study was to investigate whether these adverse factors could induce changes in Staufen expression, and whether these changes are correlated with cognitive impairments. In our study, CD-1 mice were randomly assigned to five groups: LPS, LPS+S, LPS+E, CON, and CON+S. The experiment set two age group: 3-month-old (young) and 15-month-old (middle-aged). Cognitive function was evaluated using the Morris water maze test, and Staufen expression at both the protein and mRNA level was examined using immunohistochemistry/western blotting and RNAscope technology, respectively. The results showed that middle-aged CON mice had worse cognitive performance and higher Staufen protein and mRNA levels than young CON mice. Prenatal exposure to maternal inflammation and youth stress accelerated cognitive impairment and increased Staufen expression in the aged mice, whereas enriched environment mitigated these effects. Meanwhile, Staufen expression were closely correlated with cognition performance. Our findings suggested prenatal exposure to inflammation and youth psychosocial stress can accelerate age-associated learning and memory impairments, and this effect may be exerted through increased Staufen expression.